2009
DOI: 10.1111/j.1439-0264.2008.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of the Cervico‐thoracic Sympathetic System in Donkeys (Equus asinus L.)

Abstract: Five adult donkeys of both sexes, used in applied anatomy classes, and perfused with formalin for teaching purposes, constituted the study material. Ganglion cervicale caudale of the examined materials has observed to exhibit individually variable situation as to extend on the left side of the median line, at the alignment of the first and second intercostal spaces and on the right side between the level of the first and third costa. The ganglion extended more caudally on the right side of median line. The lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 4 publications
5
19
0
Order By: Relevance
“…Many previous published anatomical articles described that, there are many morphological differences in the formation of the caudal cervical ganglion between different animals; in which the caudal cervical ganglion formed by the coalescence of the last cervical and first thoracic sympathetic nerves on both sides (Dursun, 2000;Ozgel et al). In addition, Ozgel et al, observed that the caudal cervical ganglion formed bilaterally by the coalescence of the last cervical and the first and second thoracic sympathetic nerves in two donkeys, which agrees with Singh et al (2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many previous published anatomical articles described that, there are many morphological differences in the formation of the caudal cervical ganglion between different animals; in which the caudal cervical ganglion formed by the coalescence of the last cervical and first thoracic sympathetic nerves on both sides (Dursun, 2000;Ozgel et al). In addition, Ozgel et al, observed that the caudal cervical ganglion formed bilaterally by the coalescence of the last cervical and the first and second thoracic sympathetic nerves in two donkeys, which agrees with Singh et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many anatomical data reported that the caudal cervical ganglion was situated bilaterally at the level of first intercostal space (Pather et al, 2006;Ozgel et al;Evans & de Lahunta, 2013), but König & Liebich (2007) noted that the cervicothoracic ganglion lies medial to the first rib, while Ozgel et al reported that there is some variation in the position of the caudal cervical ganglion; in four donkey the location of ganglion at the first intercostal space bilaterally, while in one donkey, this ganglion was located at the level of second intercostal space on left side, while on right side was situated in a wide area, from the first and second intercostal spaces. In the present study, the left caudal cervical ganglion was situated cranial to the level of the first rib, in which the caudal margin of the ganglion was situated below the cranial margin of the first rib, while the right caudal cervical ganglion was situated at the level of the first rib and the middle cervical ganglion was situated cranioventral to the caudal cervical ganglion and at the ventrolateral margin of trachea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To adapt to the harsh conditions, the yaks have acquired many special morphological features in the long-term natural selection. Many studies showed that the location of the cranial cervical ganglion in the yaks corresponded with that of other domestic animals, whereas its shape was different (Ozgel et al, 2009;Kabak, 2007;Shao et al, 2007). Shao (2010) reported that the lingual prominence of yak tongue was greater and more developed than in cattle (Bos taurus).…”
Section: Introductionmentioning
confidence: 99%